1998
DOI: 10.1677/joe.0.1580267
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Leydig cells through a steroidogenic acute regulatory protein-independent pathway by a lipophilic factor from macrophages

Abstract: The purpose of this investigation was to study the mechanism of action of a macrophage-derived factor that stimulates steroid production by Leydig cells. This factor increased testosterone production within 30 min, and reached a half-maximal response by 6-8 h. At a maximal dose, it stimulated testosterone production 20-fold at 24 h. Its efficacy was consistently higher than that achieved with a maximal dose of human chorionic gonadotropin (hCG). However, Leydig cells treated with a maximal dose of both the mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…However, our results indicated that cordycepin could not induce StAR protein and StAR promoter expressions in MA-10 cells. Our data are somewhat inconsistent to several studies that steroidogenesis could be trigger by cAMP and StAR-independent pathways [5759]. Therefore, it is possible that the cordycepin could possibly acitvate MAPK-ERK 1/2 and PKC pathways without increasing of StAR promoter and StAR protein expression to induce steroidogenesis in MA-10 cells, which will be worth to further investigate.…”
Section: Discussioncontrasting
confidence: 93%
“…However, our results indicated that cordycepin could not induce StAR protein and StAR promoter expressions in MA-10 cells. Our data are somewhat inconsistent to several studies that steroidogenesis could be trigger by cAMP and StAR-independent pathways [5759]. Therefore, it is possible that the cordycepin could possibly acitvate MAPK-ERK 1/2 and PKC pathways without increasing of StAR promoter and StAR protein expression to induce steroidogenesis in MA-10 cells, which will be worth to further investigate.…”
Section: Discussioncontrasting
confidence: 93%
“…This macrophage-Leydig interdigitation has been documented as early as 20-30 days postnatally in rats, just prior to pubertal testosterone secretion (Christensen and Gillim 1969;Hutson 1992;Miller et al 1983). Their close proximity and cellular interdigitation has been thought to modulate the production of testosterone through lipophilic factors and/or cytokines (Hales 2002;Hutson 1998;Lukyanenko et al 1998;Watson et al 1994). Some cytokines (including interleukin-1, tumor necrosis factor-α, interleukin-6, transforming growth factor-β (TGFβ), interferon-γ, lipopolysaccharide, reactive oxygen species, and nitric oxide) are known to decrease steroidogenesis (reviewed by Hales 2002), whereas unidentified lipophilic factors seem to increase testosterone production (Hutson 1998).…”
Section: Cells Of the Interstitiummentioning
confidence: 98%
“…A number of studies have also focussed on deciphering the mechanism involved in macrophage regulation of Leydig cell function. Using macrophage‐conditioned media a lipophilic factor has been identified (Hutson et al ., 1996) which appears to alter Leydig cell androgen synthesis through a StAR‐independent pathway (Lukyanenko et al ., 1998). …”
Section: Macrophagesmentioning
confidence: 99%